Information technology in librarianship : new critical approaches - Leckie, Gloria J.; Buschman, John. (Westport, Conn. : Libraries Unlimited, 2009)
This volume seeks to highlight a series of broader theoretical approaches and traditions in which many of the old and new critical approaches are rooted.
Introduction : information technologies and libraries : why do we need new critical approaches? / John E. Buschman and Gloria J. Leckie -- Critical theory of technology : an overview / Andrew Feenberg -- Surveillance and technology : contexts and distinctions / Gary T. Marx -- Cycles of net struggle, lines of net flight / Nick Dyer-Witheford -- A quick digital fix? : changing schools, changing literacies, persistent inequalities : a critical, contextual analysis / Ross Collin and Michael W. Apple -- Theorizing the impact of ITon library-state relations / Sandra Braman -- The prospects for an information science : the current absence of a critical perspective / John M. Budd -- Librarianship and the labor process : aspects of the rationalization, restructuring, and intensification of intellectual work / Michael F. Winter -- "Their little bit of ground slowly squashed into nothing" : technology, gender, and the vanishing librarian / Roma Harris -- Children and information technology / Andrew Large -- Open source software and libraries / Ajit Pyati -- Technologies of social regulation : an examination of library OPACs and Web portals / Gloria J. Leckie, Lisa Given, and Grant Campbell -- Libraries, archives, and digital preservation : a critical overview / Dorothy A. Warner -- Conclusion : just how critical should librarianship be of technology? / John E. Buschman.
Includes bibliographical references and index.
osc 09/05/13
Loans
Keywords: Libraries -- Information technology